Determination ofCoherenceandPhaseDifferencebetween Wind versus Current60 mand Current 60 mversusCurrent 100 mUsingCrossCorrelation in OmbaiStrait, East Nusa Tenggara - Sabhan, Sabhan (Gravitasi, 2014)
Abstract Â  Data analysis was performed to see coherence and phase difference between the wind versus current 60 m and current 60 m versus current 100 m using cross correlation in Ombai Strait, East Nusa Tenggara. Velocity components U and V of wind and current of wind data and the current were filtered in order to obtain new data on the initial data at any position of t from xt-nÂ  to xt+n. Energy spectrum density of the filter result is determined to examine the fluctuations of wind energy and real currents. Cross-correlation between wind versus current 60 m and current 60 m versus current 100 m is to determine the coherence and the phase difference of the data with the same time interval. Low coherence values in the cross-correlation between the Zonal Wind and the Zonal current at a depth of 60 m indicates that the fluctuations between the Zonal Wind and the zonal current depth of 60 m does not have a strong correlation with the largest coherence value that is 0.55 with a time leg 34 days. With fluctuation current at a depth of 60 m precedes wind fluctuation with a phase difference of 34 days. Keywords: coherence, phase difference, Ombai Strait